2008
DOI: 10.1163/156854108783900267
|View full text |Cite
|
Sign up to set email alerts
|

The early embryonic development of the satellite organism Pristionchus pacificus: differences and similarities with Caenorhabditis elegans

Abstract: Summary -As a comparative counterpart for the model organism Caenorhabditis elegans, the nematode Pristionchus pacificus was established as a satellite organism to study developmental processes. However, these studies mainly focused on post-embryonic development and little is known about the early embryonic development. Using 4D microscopy we reconstructed the early embryonic cell lineage of 12 individuals of P. pacificus. By analysing several parameters of early development, including the division sequence, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…The first description of the early embryonic cell-lineage of a nematode, that of Ascaris (Spirurina within Chromadorea) in the 1880’s [5,6], conforms to the C. elegans model. Early development across all suborders of the Rhabditida is very similar [7,8]. In general, only minor variations of the division pattern observed in C. elegans have been described in these nematodes [9,10], including heterochrony in the timing of cell divisions, and restrictions in cell-cell interaction due to different placement of blastomeres in the developing embryo.…”
Section: Introductionmentioning
confidence: 99%
“…The first description of the early embryonic cell-lineage of a nematode, that of Ascaris (Spirurina within Chromadorea) in the 1880’s [5,6], conforms to the C. elegans model. Early development across all suborders of the Rhabditida is very similar [7,8]. In general, only minor variations of the division pattern observed in C. elegans have been described in these nematodes [9,10], including heterochrony in the timing of cell divisions, and restrictions in cell-cell interaction due to different placement of blastomeres in the developing embryo.…”
Section: Introductionmentioning
confidence: 99%
“…We found that the earliest response to ZTDO occurs when synchronized embryos are exposed for at least 2 h, in which 40% of the embryos arrest. These embryos are between 120 and 180 min old and correspond to the start of gastrulation at the 28-cell stage, approximately 185 min after fertilization (Vangestel et al, 2008). Lethality reaches 100% when exposure is extended to 4 h ( Fig.…”
Section: Ztdo Is a Potent Embryocidementioning
confidence: 98%
“…Embryos synchronized to an hour range from two to 16 cells at 20°C ( Fig. 2A-E) and P. pacificus embryogenesis requires 24 h at 20°C, compared with 18 h for C. elegans (Felix et al, 1999;Vangestel et al, 2008). The proportion of unhatched eggs, including unfertilized oocytes and spontaneously arrested embryos, are counted after 26 h ex utero.…”
Section: Ztdo Is a Potent Embryocidementioning
confidence: 99%
“…Closely related species in the Elegans supergroup show nearly identical cell lineages to those of C. elegans (Zhao et al, 2008;Levin et al, 2012). Similarly, Pristionchus pacificus, which belongs to clade 9, along with the Caenorhabditis species, shows a similar pattern of early embryonic division, differing mostly in cell cycle timing (Vangestel et al, 2008). Nevertheless, it has been shown that early embryonic development is highly divergent in Nematoda, especially in the basal Enoplae (clades 1 and 2).…”
Section: Variation In Endoderm Developmental Strategiesmentioning
confidence: 99%
“…Cellular patterning during midembryogenesis is similar in nematodes from distant clades, despite extensive variation in early division (Schulze and Schierenberg, 2011). In many nematode species, the endodermal daughters migrate from the ventral side into the interior of the embryo during gastrulation, as in C. elegans (Figure 2; Vangestel et al, 2008;Schulze and Schierenberg, 2011;Schulze et al, 2012;Calderón-Urrea et al, 2016). This is followed by proliferation and polarization of the intestine primordia, and subsequent formation of lumen through cell rearrangements and remodeling, similar to gut morphogenesis observed in zebrafish (reviewed in Nowotschin et al, 2019).…”
Section: Developmental Hourglass Model: Plasticity and Conservation Omentioning
confidence: 99%